2015
DOI: 10.1051/0004-6361/201526988
|View full text |Cite
|
Sign up to set email alerts
|

Resolved gas cavities in transitional disks inferred from CO isotopologs with ALMA

Abstract: Context. Transitional disks around young stars with large dust cavities are promising candidates to look for recently formed, embedded planets. Models of planet-disk interaction predict that young planets clear a gap in the gas while trapping dust at larger radii. Other physical mechanisms might also be responsible for cavities. Previous observations have revealed that gas is still present inside these cavities, but the spatial distribution of this gas remains uncertain. Aims. We present high spatial resolutio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
198
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(229 citation statements)
references
References 61 publications
29
198
2
Order By: Relevance
“…However, we note that Carmona et al (2014) estimated g/d = 4 from detailed modeling of line observations, which would imply a strong gas depletion throughout the disk. In contrast with van der Marel et al (2016) who obtained g/d = 80 from CO line and dust continuum observations with ALMA. Figure 12 shows the calculated Toomre parameter as function of disk radius with a minimum of ∼10 around 80 au which is an order of magnitude above the Toomre criterion when a gasto-dust ratio of 100 is used.…”
Section: The Origin Of the Spiral Armsmentioning
confidence: 70%
See 2 more Smart Citations
“…However, we note that Carmona et al (2014) estimated g/d = 4 from detailed modeling of line observations, which would imply a strong gas depletion throughout the disk. In contrast with van der Marel et al (2016) who obtained g/d = 80 from CO line and dust continuum observations with ALMA. Figure 12 shows the calculated Toomre parameter as function of disk radius with a minimum of ∼10 around 80 au which is an order of magnitude above the Toomre criterion when a gasto-dust ratio of 100 is used.…”
Section: The Origin Of the Spiral Armsmentioning
confidence: 70%
“…We assume a Keplerian disk, optically thin temperature profile and estimate the disk mass from the optically thin ALMA band 7 (0.85 mm) dust continuum . The disk mass is given by ) with a typical gas-todust ratio of g/d = 100, g/d = 80 (van der Marel et al 2016), and g/d = 4 (Carmona et al 2014). The dashed lines show the 25 au scattered light cavity, the 46 au millimeter cavity from Andrews et al (2011), and the outer radius at which the spiral arms are visible.…”
Section: The Origin Of the Spiral Armsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas usually also features a cavity, but with a lower depletion factor than the millimeter emission (e.g., Bruderer et al 2014;van der Marel et al 2015van der Marel et al , 2016Canovas et al 2016). In this paper, we report ALMA observations at 1.3 mm of the transition disk around SR 24S of the dust-continuum emission and the molecular lines 13 CO (J=2-1) and C 18 O (J=2-1).…”
Section: Introductionmentioning
confidence: 93%
“…Recent observations of the radial gas density profiles interior to the asymmetries have found that some of these regions are depleted, favouring the latter idea that planet-induced vortices are responsible for the asymmetric structures in some transition discs (van der Marel et al 2016). In this case, a giant planet clears out a gap in the disc, creating sharp peaks in the radial density profile at each gap edge.…”
Section: Introductionmentioning
confidence: 99%